Virologic outcomes with tenofovir-lamivudine-dolutegravir in adults failing PI-based second-line ART - Ying Zhao; Jacqueline Voget; Isaac Singini; Zaayid Omar; Vanessa Mudaly; Andrew Boulle; Gary Maartens; Graeme Meintjes (AOSIS, 2024)
Background: In South African antiretroviral guidelines, selected patients failing second-line protease inhibitor (PI)-based therapy qualify for genotypic resistance testing - those with PI resistance receive darunavir-based third-line regimens; those without PI resistance continue current regimen with adherence support. The Western Cape province, from September 2020, implemented a strategy of tenofovir-lamivudine-dolutegravir (TLD) for patients, provided there was no tenofovir resistance, irrespective of PI resistance. Objectives: To evaluate virologic outcomes with TLD among adults failing second-line PI regimens with no tenofovir resistance. Method: An observational cohort study comparing outcomes in patients switched to TLD with those continuing the same PI or switched to darunavir-based regimens. Follow-up was until virologic suppression (HIV-1 RNA 400 copies/mL), or at the point of censoring. Results: One hundred and thirty-three patients switched to TLD, 101 to darunavir-based regimens, and 121 continued with the same PI. By 12 months, among patients with PI resistance, 42/47 (89%) in the TLD group had HIV-1 RNA 400 copies/mL compared to 91/99 (92%) in the darunavir group (hazard ratio, 1.11; 95% confidence interval, 0.77-1.60). In patients without PI resistance, 66/86 (77%) in the TLD group had HIV-1 RNA 400 copies/mL compared to 42/120 (35%) in those continuing with the same PI (hazard ratio, 4.03; 95% confidence interval, 2.71-5.98). Two patients receiving TLD developed virologic failure with high-level dolutegravir resistance. Conclusion: Amongst patients failing second-line PI with no PI resistance, switching to TLD was associated with higher virologic suppression, likely due to improved adherence. Virologic outcomes were similar in patients with PI resistance switched to darunavir-based regimens or TLD.